Twenty-four hour intraocular pressure monitoring with the SENSIMED Triggerfish contact lens: effect of body posture during sleep. Issue 10 (7th March 2017) - Beltran-Agulló, Laura; Buys, Yvonne M; Jahan, Farzana; Shapiro, Colin M; Flanagan, John G; Cheng, Jason; Trope, Graham E
Abstract : Purpose: To determine the difference in relative intraocular pressure (IOP) measured by the SENSIMED Triggerfish (TF) contact lens in flat compared with 30° head-up sleeping positions in patients with progressive primary open-angle glaucoma or normotensive glaucoma, based on recent or recurrent disc haemorrhage. Design: Prospective, randomised, cross-over, open-label comparative study. Methods: IOP was monitored for 24 hours using TF on two separate sessions. Patients were randomly assigned to sleep flat one night and 30° head-up the other. Outputs in arbitrary units were obtained. Sleep and wake periods were defined as 22:00–6:00 and 8:00–22:00, respectively. Mean TF values during sleep and wake periods and wake–sleep and sleep–wake slopes were calculated for each session. TF output signals were compared between positions. Results: Twelve subjects completed the study. Significant mean positive slopes were noted during the sleep period for both positions (p<0.01). No significant differences in the TF mean values were observed between positions (p=0.51). Six (54%) subjects had mean TF values significantly higher during the flat supine session, while four (36%) subjects had higher values during the head-up session. A significant increase in Goldmann IOP (p=0.001) and TF (p=0.02) measurements were observed after 24 hours of TF wear ('drift phenomenon'). Conclusions: Sleep position affects IOP as measured by TF in some patients with progressive glaucoma. The upward drift in TF output detected in >50% of the subjects requires further investigation to establish whether the increased output values over time are an artefact induced by the TF or a real change in IOP. Trial registration number: NCT01351779